1989
DOI: 10.1210/endo-125-1-524
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormones Modulate Thyrotropin-Releasing Hormone Biosynthesis in Tissues Outside the Hypothalamic-Pituitary Axis of Male Rats*

Abstract: In the present study we have examined the in vivo effects of thyroid hormone and TRH on secretory tissue concentrations of TRH and TRH-Gly (pGlu-His-Pro-Gly), a TRH precursor. Within secretory granules, TRH-Gly is converted to TRH through alpha-amidation of the C-terminal proline residue, using Gly as the NH2 donor. Using specific RIA, we measured the TRH-Gly immunoreactivity (TRH-Gly-IR) and TRH-IR concentrations in tissues from the reproductive and gastrointestinal systems, adrenals, and other internal organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…The 100-and 300-fold greater levels of TRH-Gly-IR com pared to the TRH-IR levels in human CSF is similar to the cor responding ratio in extrahypothalamic tissue extracts [8,9] but this ratio is essentially reversed in extracts of brain tissue [17,22]. Possible explanations for the unexpectedly high values of TRH-Gly-IR in CSF include (I) extra-CNS tissues secrete TRH-containing vesicles with a high proportion of TRH-Gly-IR into the CSF, and (2) the TRH-Gly-binding substance of CSF protects TRH-Gly from enzymatic degradation while TRH re mains unprotected and subject to rapid destruction.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The 100-and 300-fold greater levels of TRH-Gly-IR com pared to the TRH-IR levels in human CSF is similar to the cor responding ratio in extrahypothalamic tissue extracts [8,9] but this ratio is essentially reversed in extracts of brain tissue [17,22]. Possible explanations for the unexpectedly high values of TRH-Gly-IR in CSF include (I) extra-CNS tissues secrete TRH-containing vesicles with a high proportion of TRH-Gly-IR into the CSF, and (2) the TRH-Gly-binding substance of CSF protects TRH-Gly from enzymatic degradation while TRH re mains unprotected and subject to rapid destruction.…”
Section: Discussionsupporting
confidence: 55%
“…Alpha-amidation of pGlu-His-ProGly (TRH-Gly) is the final, and in most tissues, rate-limiting step in TRH biosynthesis [8,9]. Experiments using an antibody directed against TRH-Gly indicated that, in some tissues, the levels of this TRH precursor can be more than 100-fold higher than those for TRH [8].…”
mentioning
confidence: 99%
“…Still to be understood in this scenario is the precise cell population(s) involved in TRH production, and the nature of the inductive signal for TRH-Gly conversion to TRH; i.e., whether it is mediated by external Ag-driven stimuli or whether signals from the host "feed in" during the early phase of the immune-endocrine process. Some evidence for an internal signal currently exists from experiments which demonstrate increased TRH-Gly levels following thyroid hormone (T 3 or T 4 ) stimulation (57). Additional studies aimed at delineating the participation of TRH and other peptide mediators can be done using the hormoneresponsive cells described here to understand the functional involvement of immune-endocrine interactions on the immune response.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have indicated the presence of TRH in rat adrenal gland (Simard et al 1989;Fuse et al 1990), but its cellular localization and physiological significance were unknown. The present study demonstrates that adrenal TRH derives from a precursor molecule similar or closely related to hypothalamic pro-TRH.…”
Section: Discussionmentioning
confidence: 99%
“…Although TRH in pharmacological concentrations has been demonstrated to exert multiple effects on tissues other than the pituitary, the physiological significance of the peripheral TRH and the respective contribution of each tissue from which it comes have not been clearly established. In that regard, TRH has been identified in extracts of rat adrenal glands (Simard et al 1989;Fuse et al 1990), but the cellular localization of TRH immunoreactivity and whether adrenal and neural pro-TRHs are identical remain unknown. In the present study we investigated the presence of both TRH and a prepro-TRH connecting peptide, the prepro-TRH[160-169] (Ps4), in rat adrenal glands by combining molecular sieve filtration and HPLC with EIA detection.…”
mentioning
confidence: 99%